Trends in Research on Self-Efficacy in Mathematics Education: A Bibliometric Analysis for 2013–2025 - Nike Astiswijaya; Turmudi Turmudi; Kusnandi Kusnandi; Dadang Juandi (ISEJ : Indonesian Science Education Journal, 2026)
Self-efficacy has been one of the most widely used psychological constructs in mathematics education research for over three decades. However, the development of research, the intellectual structure of the field, and its relationship to learning approaches and mathematical competence have not been comprehensively developed. This study aims to analyze publication trends, thematic structures, and identify research gaps regarding self-efficacy in mathematics education. The study uses a bibliometric approach to 3,096 Scopus Open Access documents from 2013–2025 that have been screened to ensure their relevance to the field of education. The analysis was conducted using Bibliometrix (R) to broadcast publication performance and VOSviewer to map the co-word network. The results show sharp and consistent growth (Annual Growth Rate 20.47%), with Frontiers in Psychology as the most published platform (197 documents) while EURASIA Journal of Mathematics, Science and Technology Education remains the most relevant core journal for the mathematics education audience specifically. The co-word mapping identified four thematic clusters—self-efficacy, mathematics teaching and achievement; health and behavior; clinical education and medical competence; as well as procedures and pilot studies. However, the most pedagogically significant finding is the lack of explicit integration between self-efficacy, team-based learning, and mathematical communication in the context of statistics education: combined phrases such as ‘collaborative learning in statistics’ and ‘communication skills in mathematics’ were completely absent (n = 0) among all the documents analyzed, while the individual terms rarely appeared alongside self-efficacy. This finding confirms that research interventions that integrate collaborative learning with self-efficacy strengthening in statistics courses—particularly in higher education contexts that are still underrepresented in the global literature such as Southeast Asia—represent a pressing research agenda and have the potential to make significant pedagogical contributions to the teaching of mathematics and statistics in higher education.